67.3: New Driving Method for Reducing Eye Strain Technology (REST) in Displaying Still Image Using CAAC IGZO LC Display. Issue 1 (1st July 2013) - Miyake, Hiroyuki; Kaneyasu, Makoto; Hatsumi, Ryo; Nishi, Takeshi; Hirakata, Yoshiharu; Koyama, Jun; Yamazaki, Shunpei; Chubachi, Yuka; Katayama, Masahiro
Abstract We applied a method for extending an interval between data rewrite operations in displaying still images to various combinations of liquid crystal materials and alignment films, and confirmed that this method suppressed flickers in data rewriting. Extending this interval during still image display will reduce eye strain.